1998
DOI: 10.1152/jappl.1998.85.3.867
|View full text |Cite
|
Sign up to set email alerts
|

Zero-stress states of human pulmonary arteries and veins

Abstract: The zero-stress states of the pulmonary arteries and veins from order 3 to order 9 were determined in six normal human lungs within 15 h postmortem. The zero-stress state of each vessel was obtained by cutting the vessel transversely into a series of short rings, then cutting each ring radially, which caused the ring to spring open into a sector. Each sector was characterized by its opening angle. The mean opening angle varied between 92 and 163 degrees in the arterial tree and between 89 and 128 degrees in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 21 publications
1
18
1
Order By: Relevance
“…The zero-stress state after cutting was calculated as the angle () of opening of the resting artery. Despite evidence that the opening angles at the zero-stress states vary in third-to ninth-order human PA (27), we found that the opening angles at the zero-stress states were comparable between left and right branches of intrapulmonary arteries (94.2 Ϯ 9.10 vs. 88.2 Ϯ 7.6°; P ϭ 0.6218).…”
Section: Resultscontrasting
confidence: 91%
“…The zero-stress state after cutting was calculated as the angle () of opening of the resting artery. Despite evidence that the opening angles at the zero-stress states vary in third-to ninth-order human PA (27), we found that the opening angles at the zero-stress states were comparable between left and right branches of intrapulmonary arteries (94.2 Ϯ 9.10 vs. 88.2 Ϯ 7.6°; P ϭ 0.6218).…”
Section: Resultscontrasting
confidence: 91%
“…Extensive data have been published on stress-strain distributions of the major vessels (Fung, 1991(Fung, , 1993Fung and Liu, 1995;Han and Fung, 1996;Huang and Yen, 1998;Fung, 1988, 1992;Lu et al, 2001;Rachev et al, 1998;Zhao et al, 2000;Zhou and Fung, 1997). It is now well documented that the vascular system expresses residual strain in the no-load state Liu and Fung, 1988Zhao et al, 2000Zhao et al, , 2002.…”
Section: Biomechanical Properties Of the Saphenous Veinmentioning
confidence: 99%
“…The structure of the pulmonary network ( Figure 2) was reconstructed on the basis of reported clinical investigations [8,9]. Implementation of the systemic circulation structure ( Figure 3) is more tedious.…”
Section: D Network Blood Flow Modelmentioning
confidence: 99%